Waylon! : the most awesome of all - Pennypacker, Sara, 1951- (Pennypacker, Sara, 1951- Waylon, 2019)
"Waylon gives up a chance to meet Neil DeGrasse Tyson to help his sister, his father, and a friend when they need him most, but gains a much greater reward." --